Long-term efficacy and safety of alemtuzumab in participants with highly active MS: TOPAZ clinical trial and interim analysis of TREAT-MS real-world study - Tjalf Ziemssen; Ann D. Bass; Bart Van Wijmeersch; Sara Eichau; Stephan Richter; Frank Hoffmann; Nicole M. Armstrong; Magdalena Chirieac; Janete Cunha-Santos; Barry A. Singer (Therapeutic Advances in Neurological Disorders)
Background: Alemtuzumab is a disease-modifying therapy for highly active relapsing-remitting multiple sclerosis (RRMS). Sustained efficacy up to 9 years was observed in the phase IIIb/IV open-label TOPAZ clinical trial and assessed in the real-world retrospective and prospective study, TREAT-MS. Objectives: To examine long-term efficacy and safety of alemtuzumab in participants with multiple sclerosis (MS) and highly active disease (HAD) by combining up to 13 years of TOPAZ data and TREAT-MS interim data. Design: TOPAZ: Randomized participants completing core CARE-MS I and II could receive additional alemtuzumab (12 mg/day, 3 consecutive days; ⩾12 months apart) for 11–13 years after initiating treatment. TREAT-MS: Participants from German MS clinics were observed for 4 years after last alemtuzumab treatment phase. Methods: Efficacy outcomes (annualized relapse rate (ARR), change in Expanded Disability Status Scale (EDSS), 6-month confirmed disability worsening/improvement, magnetic resonance imaging), and adverse events (AEs) were examined. Primary HAD definition (⩾2 relapses in the year prior to baseline and ⩾1 gadolinium-enhancing lesion at baseline), and two alternative HAD definitions were assessed. Results: More participants from CARE-MS I (28%) and II (24%) met primary HAD criteria than TREAT-MS (~14%). Mean ARR for alemtuzumab-treated HAD participants was significantly reduced in CARE-MS I and II (0.14 and 0.15, respectively, Years 3–13) and in TREAT-MS (0.24, > 2 years). Stable/improved EDSS scores were achieved by 74% of HAD participants in CARE-MS I, 67% in CARE-MS II (both Year 11), and 79% in TREAT-MS (Year 3.6), with 6-month CDI achieved by about half at Year 11 (CARE-MS I, II). Annual treatment-emergent AE incidences declined in TOPAZ and were lower in TREAT-MS. Conclusion: Sustained efficacy of alemtuzumab was observed for clinical and radiological outcomes in participants with HAD in the TOPAZ clinical trial and real-world TREAT-MS study with no new safety signals. Trial registration: ClinicalTrials.gov (CARE-MS I, NCT00530348; CARE-MS II, NCT00548405; CARE-MS Extension Study, NCT00930553; TOPAZ, NCT02255656). Paul-Ehrlich-Institut (TREAT-MS, NIS 281).